4x-3*-3=7

Simple and best practice solution for 4x-3*-3=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3*-3=7 equation:


Simplifying
4x + -3 * -3 = 7

Multiply -3 * -3
4x + 9 = 7

Reorder the terms:
9 + 4x = 7

Solving
9 + 4x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 4x = 7 + -9

Combine like terms: 9 + -9 = 0
0 + 4x = 7 + -9
4x = 7 + -9

Combine like terms: 7 + -9 = -2
4x = -2

Divide each side by '4'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 3x+13=39-5x | | 17x-17+31+9x-69-18x=-39 | | 4x+-3=-1 | | 5+2y=19 | | 9x+3-3x+1=0 | | 2[(4x-2)(4x-2)]=120 | | 6d+4=4d+12 | | x^2+2x^2=400 | | 5z+20-2z=38 | | 4x^2-7x-2= | | 162-5x=5x+22 | | 5(z+4)-2z=38 | | -16x^2=32 | | 88-2=10x+16 | | 9-y=y+5 | | 2x^2+5x+4=x+4 | | 2(y-2)=6 | | 4b+4=7b-5 | | 8(x-7)=x(x-7) | | (10x-4)(3x+2)=0 | | 3a+1=5a-3 | | 4z+2=10z-1 | | c-1=2c-8 | | b+3=3b+1 | | 10a+1=8a+9 | | 3c-2=2c+4 | | -x^2+3x-1=0 | | (5-2x)+(4x-13)=2 | | 2b-7=b-3 | | x-3+9(8-6)= | | 3a+1=a+7 | | 5.6+1.6= |

Equations solver categories